Preparation, structure, cytotoxicity and mechanism of action of ferritin-Pt(II) terpyridine compound nanocomposites. (3rd December 2018) - Ferraro, Giarita; Pica, Andrea; Petruk, Ganna; Pane, Francesca; Amoresano, Angela; Cilibrizzi, Agostino; Vilar, Ramon; Monti, Daria Maria; Merlino, Antonello
Aim: A Pt(II)-terpyridine compound, bearing two piperidine substituents at positions 2 and 2′ of the terpyridine ligand (1 ), is highly cytotoxic and shows a mechanism of action distinct from cisplatin.1 has been incorporated within the ferritin nanocage (AFt).Materials & methods: Spectroscopic and crystallographic data of the Pt(II)–AFt nanocomposite have been collected and in vitro anticancer activity has been explored using cancer cells.Results: Pt(II)-containing fragments bind His49, His114 and His132. Pt(II)–AFt nanocomposite is less cytotoxic than1, but it is more toxic than cisplatin at high concentrations. The Pt(II)–AFt nanocomposite triggers necrosis in cancer cells, as free1 does.Conclusion: Pt(II)–AFt nanocomposites are promising vehicles to deliver Pt-based drugs to cancer cells.